Training community health volunteers to use mobile platform during the COVID-19 pandemic: The Kenya experience - Anne W. Mbwayo; Muthoni Mathai; Teresia Mutavi; Stella Waruinge; Noah Triplett; Tessa Concepcion; Pamela Y. Collins; Shannon Dorsey (Cambridge Prisms: Global Mental Health, 2024)
This study describes an alternative to face-to-face training method for community health volunteers (CHVs) as used by a collaborative group from the University of Nairobi, University of Washington and the Nairobi Metropolitan Mental Health Team during the COVID-19 lockdown in Kenya. This qualitative study describes the experiences of 17 CHVs enrolled in a training study, required to utilize different digital platforms (Google Meet or Jitsi) as a training forum for the first time. Verbatim extracts of the participants’ daily experiences are extracted from a series of write-ups in the group WhatsApp just before the training. Daily failures and success experiences in joining a Google meet or Jitsi are recorded. Then, 17 participants, 10 women and 7 men, aged between 21 and 51 years (mean = 33), owning a smartphone, were enrolled in the study. None had used Jitsi or Google meet before. Different challenges were reported in login to either and a final decision to use Jitsi, which became the training platform. Training CHVs to deliver a psychosocial intervention using smartphones is possible. However, the trainer must establish appropriate and affordable methods when resources are constrained.